Reshaping perspectives of deep-sea benthic function - Sturdivant, S. Kersey; Guarinello, Marisa L.; Germano, Joseph D.; Carey, Drew A. (Frontiers in Marine Science, 2024)
Bioturbation is a key ecosystem function with a fundamental role in mediating major biogeochemical cycles. The intensity and depth of bioturbation is influenced by the taxa present, which is often a function of food supply. The deep sea is generally oligotrophic with sediments composed predominantly of small, shallow burrowing macrofauna (<10 cm). Human activity is increasingly introducing POC to the deep-sea, however, organic enrichment of the deep-sea, and the subsequent response of bioturbators is poorly understood. Here we present data on benthic function in deep-sea systems that have experienced organic enrichment. We show that organic enrichment enhances deep-sea bioturbation through larger, advanced successional taxa, and deeper bioturbation depths. Enhanced bioturbation in the deep-sea should confer positive ecosystem functions (nutrient recycling, microbiological activity, remineralization), but adherence to approaches and interpretations guided by the paradigm of small, shallow-burrowing infauna could significantly underestimate deep-sea benthic processes at a global scale.Evidence showing anthropogenic organic enrichment of the deep-sea enhances deep-sea function by stimulating bioturbation.The deep sea (>1000 m water depth) is the most extensive habitat on our planet (Snelgrove 1997, Danovaro 2017) and plays a critical role in global ecosystem function via its influence on the biological pump and nutrient recycling (Snelgrove et al. 1997, Ramírez-Llodra et al. 2011, Thurber et al. 2014). More than 60% of the Earth's surface is below 1000 m of water (Glover and Smith 2003); from about 1000 m to the deepest depths of the ocean floor there is virtually no seasonal variation and water temperatures are consistently ~2 o C (Rex and Etter 2010). This once remote ecosystem is threatened by the cumulative effects of anthropogenic activities (e.g., climate change; fisheries; oil, gas, and mineral extraction), which could result in ecological impairment and potentially catastrophic regime-shifts (Levin and Le Bris 2015, Wedding et al.* A linear regression was conducted to determine if there was a correlation between TOC% and Bioturbation Depth. This analysis utilized station location independent data, and the residuals were determined to be random, (i.e. independent variables drawn from a normal [0, sigma] distribution).